Colloidal transport and deposition through dense vegetation. (January 2022) - Yu, Congrong; Duan, Peiyi; Barry, D.A.; Johnson, William P.; Chen, Li; Yu, Zhongbo; Sun, Yufeng; Li, Ying
Abstract: The effectiveness of submerged synthetic aquatic vegetation on removal of colloids from flowing water was investigated to explore retention of particulate nonpoint source pollutants in aquatic systems. In colloid transport experiments, the deposition rate coefficient of colloids in dense vegetation is often taken as spatially constant. This assumption was tested by experiments and modeling aimed at quantifying changes in colloid retention with travel distance in submerged synthetic aquatic vegetation. Experiments were performed in a 10-m long, 0.6-m wide flume with a 5-cm water depth under different fluid velocities, initial colloid concentrations, and solution pH values. A model accounting for advection, dispersion and first-order kinetic deposition described the experimental data. The colloid deposition rate coefficient showed a power-law decrease with travel distance, and reached a steady state value before the end of the flume. Measured changes in colloid properties with transport distance (ζ potential and size) could not explain the observed decrease. While gravity was shown to contribute to the decrease, its impact was too weak to explain the decreasing power law trend, suggesting that processes operating in granular media to produce similar outcomes may also apply to submerged vegetation. Graphical abstract: Image 1 Highlights: Colloid deposition rate decreased with travel distance following an approximate power law under various flow conditions. Gravity contributed to the decrease, but could not explain its magnitude. Mechanisms driving decreased deposition rate coefficient in granular media may also apply to submerged vegetation.